Desarrollo de un serious game como herramienta educativa escolar - Saquinga Guishcasho, Erik David (2019)
The learning problems generated in the primary education context delay the children’s educational process, which gets a delay in the academic performance that often causes the failure of the school year. Due to the limited use of methodological education tools in the classroom for training processes, the inadequate implementation of strategies and technologies that help feedback the learning process. Children are ready to use technological devices with psycho-pedagogical elements, which help to understand educational content by improving the procedures and activities generated in the classroom. Therefore, it is proposed to create a serious game that serves as a support tool for teachers in the learning process to contribute and mitigate problems in the school. The result is a dynamic and accessible application with educational content that is easy to access and manipulate for children, teachers, and parents. For the development of the serious game, software engineering methodologies were used that allowed the fast and reliable development of it, in addition to the use of JAVA, for the development of an educational game on a web platform through graphic tools that are part of its environment. It is concluded that this kind of serious game will serve as a support tool in the learning-teaching processes among children from 6 to 8 years of age.